Construction of otherness in the CBS’s sitcom, the big bang theory - Amerian, S; Marzban, B (Khate Sefid Publications)
The fact that TV enjoys a great number of viewers, many of whom are influenced by it is undeniably acknowledged. This paper analyses the successful American sitcom, The Big Bang Theory, and investigates the factor of Otherness and Orientalist representation of an Indian character named Raj Koothrappali in the series. Employing content analysis, the authors investigated how the character was represented, and his culture, religion, beliefs, values and appearance were taken into account. The aim was to see if there was still misrepresentation of other nations and their cultures and beliefs in the 21st century television. It was concluded that despite this series being a situation comedy and having humorous tone and display, there is more than just humor when we look in depth at the way the Otherness is represented in the show by depicting this ethnic Indian character. Abundance of material were found to project stereotypical constructions and the fact that this character is seen as an “Other” by the creators of the show and at times even distanced from his American friends whether through his sense of clothing or sitting alone on the ground while others are seated on chairs or his feminine qualities.
Keywords: orientalism, media representation, situation comedy, Indian culture and religion, otherness